(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2026)
Purpose: The present study intents to create and validate a Spiritual Intelligence Scale for higher secondary students. It aims to evaluate spiritual intelligence as a multidimensional construct that facilitates meaning-making, self-awareness, existential reflection, and personal growth among adolescents. The study also vision to establish a reliable and valid measurement tool apt for educational and psychological research contexts. Methodology: This study adopts a quantitative research structure with a scale development and psychometric validation approach. Data were collected from 150 higher secondary students from government, aided, and unaided schools in Kottayam District, Kerala, selected using stratified random sampling. An initial pool of 15 items was developed based on an extensive review of literature and expert validation. The instrument was tested using reliability analysis, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA) to examine its psychometric properties and validate the factor structure. Findings/Result: The outcome of the study revealed satisfactory internal consistency with an overall Cronbach’s alpha of 0.815. EFA led to the removal of five items and identified a three-factor structure comprising Existence of Critical Thinking, Discovery of Personal Meaning, and Conscious State of Expansion. CFA confirmed the adequacy of the measurement model, with all goodness-of-fit indices meeting recommended thresholds. The standardized factor loadings and regression weights were statistically significant, confirming strong construct validity. Originality/Value: This study contributes to the development of a context-specific and psychometrically validated Spiritual Intelligence Scale for higher secondary students. It provides a reliable instrument for further research in educational psychology and enhances understanding of spiritual intelligence as a key factor in adolescent development and well-being. Paper Type: Empirical Research Paper.